The Influence of Motivation, Work Environment, Competence on Job Satisfaction and Job Performance - Inez Angelina; Yohana F. Cahya Palupi Meilani (PT Mattawang Mediatama Solution, 2023)
This research aims to determine the influence of motivation, work environment, competency on job satisfaction and work performance. In this research, data was obtained by distributing questionnaires to 84 respondents to obtain research data related to Motivation, Work Environment, Competence, Work Performance, Job Satisfaction. This process begins with assumptions or hypotheses which are then continued by research to obtain new theories. This paradigm has become the origin of quantitative research where the truth of an event is based on validly measurable reality. The results of this research are to provide a deeper understanding of the factors that influence job satisfaction and work performance, providing a basis for companies to design management policies and strategies aimed at increasing motivation, creating a supportive work environment, and increasing employee competence. The practical implication of this research is that companies can increase employee productivity and welfare by focusing on developing motivation, improving the work environment, and increasing competence through training and development.